2011
DOI: 10.1063/1.3593194
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic order near 270 K in mineral and synthetic Mn2FeSbO6 ilmenite

Abstract: The structural and magnetic properties of Mn 2 FeSbO 6 single-crystalline mineral and ceramic samples synthesized under thermobaric treatment have been investigated, and compared to theoretical predictions based on first-principles electronic structure calculations. This ilmenite system displays a sharp magnetic transition just below the room temperature related to a ferrimagnetic ordering of the Mn 2+ and Fe 3+ cations, which makes Mn 2 FeSbO 6 a promising candidate for designing functional magnetic materials. Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
29
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 13 publications
4
29
0
Order By: Relevance
“…MFSO cannot be synthesized under ambient pressure. Yet it was shown that MFSO ilmenite could be synthesized with relatively high purity using thermobaric treatments [6,7]. MFSO ilmenite was found to order ferrimagnetically below 270 K. By increasing the pressure employed during the thermobaric synthesis, a double perovskite phase of MFSO may be stabilized, with Mn cations on the A-site, and Fe, Sb cations ordered on the B-site.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…MFSO cannot be synthesized under ambient pressure. Yet it was shown that MFSO ilmenite could be synthesized with relatively high purity using thermobaric treatments [6,7]. MFSO ilmenite was found to order ferrimagnetically below 270 K. By increasing the pressure employed during the thermobaric synthesis, a double perovskite phase of MFSO may be stabilized, with Mn cations on the A-site, and Fe, Sb cations ordered on the B-site.…”
mentioning
confidence: 99%
“…Figure 3 (upper panels) shows the temperature T dependence of the magnetization M (plotted as M/H) for both MFSO compounds. While the ilmenite compound displays a ferrimagnetic transition near 270 K [6], perovskite MFSO (lower panel) exhibits a paramagnetic response near that temperature. On the other hand a peak is observed in the magnetization curves near 60 K, suggesting antiferromagnetic ordering below that temperature.…”
mentioning
confidence: 99%
See 3 more Smart Citations